2020
DOI: 10.1503/jpn.190039
|View full text |Cite
|
Sign up to set email alerts
|

Impaired cognitive performance under psychosocial stress in cannabis-dependent men is associated with attenuated precuneus activity

Abstract: Background: Deficient regulation of stress plays an important role in the escalation of substance use, addiction and relapse. Accumulating evidence suggests dysregulations in cognitive and reward-related processes and the underlying neural circuitry in cannabis dependence. However, despite the important regulatory role of the endocannabinoid system in the stress response, associations between chronic cannabis use and altered stress processing at the neural level have not been systematically examined. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 62 publications
0
16
0
Order By: Relevance
“…We applied the ALFF method to investigate the spontaneous brain activity alterations in patients with RD and found significant ALFF decrease in the bilateral precuneus. The precuneus, located in the posteromedial parietal lobe, is considered to play a central role in a range of highly integrated tasks, including cognitive tasks ( 29 , 30 ) and perception of self-motion ( 31 ). Some studies also showing that electrical stimulation of the precuneus may induce the symptom of dizziness ( 11 , 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…We applied the ALFF method to investigate the spontaneous brain activity alterations in patients with RD and found significant ALFF decrease in the bilateral precuneus. The precuneus, located in the posteromedial parietal lobe, is considered to play a central role in a range of highly integrated tasks, including cognitive tasks ( 29 , 30 ) and perception of self-motion ( 31 ). Some studies also showing that electrical stimulation of the precuneus may induce the symptom of dizziness ( 11 , 12 ).…”
Section: Discussionmentioning
confidence: 99%
“… Sensation seeking men (but not women) showed decreased mOFC during stress after ingesting alcohol, which predicted problem drinking at follow-up. Zhao et al (2019) N = 51 ( n = 28 cannabis users) M age = 25.05 (4.33) 100 % Male In-person screening Effects of substance use on neural function Cannabis Montreal Imaging Stress Task (MIST) Stress > No Stress Precuneus, dmPFC Cannabis users had decreased stress-related reactivity in the precuneus, and increased connectivity between the precuneus and dmPFC. Behaviorally, they performed worse in the social stress condition, but not the no-stress condition.…”
Section: Resultsmentioning
confidence: 99%
“…Beyond reward and cognitive processes, atypical stress reactivity and deficient regulation of stress are prominent risk factors for the initiation of substance use ( Chaplin et al, 2018 , Zhao et al, 2019 ), and are considered a hallmark of addiction ( Sahani et al, 2022 , Sinha, 2008 , Sinha, 2011 ). Self-report data has indicated that the regulation of negative affective states is a primary motivational drive for alcohol use ( Hussong and Chassin, 1994 ) and cannabis use ( Simons et al, 2000 ); and that these coping-oriented motivations are linked to an increased risk of addictive patterns of use ( Schlossarek et al, 2016 , Winters et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall meta-analysis encompassing data from all original studies demonstrated robust exercise-induced changes in cognition related functional activation of the left parietal lobe, primarily covering the precuneus (69.7%) and spreading into inferior (27.3%) and superior (3%) parietal lobe. The precuneus plays a key role in a range of highly integrated mental processes, ranging from basic cognitive processes to regulatory control over performance under stress 70,71 . The integrative function of the precuneus is further reflected in the functional connectivity profiles of these regions, which include separable interactions with networks engaged in sensorimotor and cognitive processes (e.g., executive function, episodic memory, visuospatial processing) 72 .…”
Section: Discussionmentioning
confidence: 99%